Cationization of cellulose nanofibrils (CNF) for application as additive to improve quality of eucalyptus kraft pulp on paper production - Gomes, Claudia Marcia (2015)
Cellulose nanofibril (CNF) refers to cellulose fibril agglomerates with diameter in the nanometer scale, obtained from cellulosic fibers by mechanical processing. Its main characteristics are high mechanical strength and transparency, in addition to the low specific weight and coefficient of thermal expansion. Another relevant factor is to be a biodegradable polymer, therefore attractive from an environmental point of view. Additionally, the surface of the CNF presents high concentration of hydroxyl groups, suitable for introducing molecules or polymers, which can improve its performances or develop new features. The CNF has been studied as a substitute for synthetic polymers in many different areas. In this study, the CNF was modified for use as an additive to produce paper, and consists of three stages. In the first stage, a literature review of surface modification of CNF was conducted. In the second stage, the CNF was cationized in order to make its distribution more homogeneous on paper structure, allowing a large number and strong bounds between the fibers. The physicochemical and ultrastructural properties of CNF before (P-CNF) and after the cationization (C1-CNF and C2-CNF) were evaluated, in order to ensure the modification process and verify its effect on the CNF structure. The CNFs presented trimethylammonium chloride content of 0.68 (C1-CNF) and 1.21 mmol·g -1 (C2-CNF). The cationization reactions decreased the fibrils thickness and the length, and also degraded the cellulose chain and crystallinity structure, these effects being more pronounced for the reaction that resulted in the C2- CNF. In the third stage, the C-CNFs were used as additive to improve quality of eucalyptus kraft pulp on paper production. The effect of adding C-CNFs on pulp drainage time and on physical-mechanical and optical properties of paper sheets was evaluated. After the cationization, the CNF presented homogeneous distribution on paper structure. Only the pulps with high charges of C-CNFs (3% and 5%) presented drainage time higher than those with P-CNF. The addition of C2-CNF resulted in pulps with drainage time statistically higher than those with C1-CNF. In general, the papers with addition of C-CNFs presented lower bulk, and higher air resistance and smoothness than those with P-CNF. Only the addition of high charges of C-CNFs resulted in papers with tear index and burst index statistically higher than those with P-CNF. A possible explanation is that larger flocs present during the paper formation can cause a greater entanglement between the fibers. When compared with P-CNF, the addition of different charges of C-CNFs did not increase the tensile index of papers. The reduction of mechanical strength for paper with low charges of C-CNFs may have occurred by rupture of the paper in the C-CNF, which was degraded during the cationic reaction. The papers with addition of different charges of C- CNF presented lower light scattering coefficient and higher transparency than those with P-CNF. In general, the degree of cationization of CNF had effect on the physical and optical properties of paper, however it had no effect on mechanical properties. For the use of cationic CNF as additive to improve quality of Eucalyptus kraft pulp on paper production, it is necessary that the cationic reaction be performed in medium compatible with paper production and does not damage the CNF structure. Additionally, the degree of cationization and the charge of CNF have to be optimized to improve the paper properties without increasing the pulp drainage time.